ANALISIS KERJASAMA AFTA DAN INDONESIA: PELUANG DAN TANTANGAN 2015-2020 - Putri, Irsya Tursina (Universitas Panca Marga, 2022)
Abstract AFTA or ASEAN Free Trade Area is a free trade area between countries that are members of ASEAN. AFTA was formed in January 1992 and officially started in 1993. AFTA is aimed at developing the potential and economic strength of ASEAN, which still has many developing countries. AFTA itself has the function of increasing the flow of investment, the flow of labour and the flow of information and technology exchange between developed and developing countries in the Southeast Asian region. The presence of AFTA is expected to empower all the potential of each country that is incorporated in ASEAN. However, AFTA which was formed by ASEAN also experiences several obstacles at present. One of the biggest obstacles is the Covid-19 pandemic. Apart from this, the trade war between China and the United States also had a significant impact on the life of AFTA as a free trade area. In this discussion, the author will discuss the challenges and opportunities faced by AFTA and also Indonesia as a member country that is actively involved both in ASEAN itself and in AFTA within 5 years, namely from 2015-2020. The author uses descriptive analytic methods or explanatory research.